CAUSES AND CONSEQUENCES OF SPEAKING ANXIETY AMONG UZBEK EFL LEARNERS: IMPLICATIONS FOR LANGUAGE TEACHING - Xalilublayeva Shahnozaxon Saminjon qizi (International Journal of Literature and Language Studies, 2026)
Speaking anxiety is one of the most persistent barriers to successful oral communication in English as a foreign language (EFL) setting. Although many learners demonstrate satisfactory knowledge of grammar and vocabulary, they often experience fear, tension, and nervousness when required to speak in English. This review article synthesizes international and local research on speaking anxiety and examines its causes, consequences, and pedagogical implications for Uzbek EFL learners. The review draws on studies conducted in different educational contexts and discusses major theoretical perspectives, including Foreign Language Classroom Anxiety and the Affective Filter Hypothesis. The analysis indicates that speaking anxiety is influenced by psychological, linguistic, social, and instructional factors. Fear of negative evaluation, fear of making mistakes, low self-confidence, insufficient vocabulary knowledge, limited opportunities for communication, and classroom practices emerge as the most commonly reported causes. The review also demonstrates that anxiety has a significant and academic achievement. Furthermore, anxiety may contribute to long-term avoidance of communication and negative attitudes toward language learning. The article argues that supportive classroom environments, communicative teaching approaches, collaborative learning activities, constructive feedback, and technology-enhanced speaking practice can reduce anxiety and improve oral communication skills. The findings provide useful insights for English language teachers in Uzbekistan and contribute to a deeper understanding of the emotional dimensions of language learning.